2020
DOI: 10.3389/fpsyg.2020.00342
|View full text |Cite
|
Sign up to set email alerts
|

Does Acute Stress Impact Declarative and Procedural Learning?

Abstract: It is well established that acute stress can influence memory function, yet its influence may differ across memory systems. Whereas stress sometimes exerts a negative influence on declarative learning, it does not necessarily harm learning in general, as demonstrated in the case of procedural learning. Probabilistic category learning is mediated by the striatum, but delaying feedback by a few seconds shifts learning to become more hippocampal-dependent. Here, we examined the influence of acute stress on this t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 65 publications
(116 reference statements)
0
3
0
Order By: Relevance
“…Several studies have indicated that chronic stress disrupts spatial learning and memory formation (Ballan and Gabay, 2020). In agreement with these reports, we also observed that CRS impairs spatial memory.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have indicated that chronic stress disrupts spatial learning and memory formation (Ballan and Gabay, 2020). In agreement with these reports, we also observed that CRS impairs spatial memory.…”
Section: Discussionmentioning
confidence: 99%
“…In our opinion, this overrates the cognitive flexibility of mice; however, it emphasizes the necessity for further assessments of a depressed state independent of immobility time. It can further be argued that other well-established animal models of depression as the Chronic Mild Stress test, produce similar outcomes; and that a depressed state or strong stressors impede, not increase learning both in humans and in animals 17,20,[26][27][28][29][30] . The burden of the animals is usually rated as high to extreme in animal research applications.…”
Section: Discussionmentioning
confidence: 99%
“…While acute stressors may impact other cognitive outcomes such as declarative memory ( Ballan and Gabay, 2020 ; Cohen et al, 2020 ), learning ( Becker and Rohleder, 2020 ; Wirz et al, 2018 ) and long-term memory ( Henckens et al, 2009 ; Klier and Buratto, 2020 ), these major domains of EF are important in various aspects of healthy and pathological behavior and serve as useful markers for investigating effects of stressors on cognitive function. The PFC plays a major role in EF; however, specific PFC subregions and their related neural pathways differ depending on the domain of EF.…”
Section: Effects Of Acute Stressorsmentioning
confidence: 99%